Effect Of Financial Leverage, Profitability And Income Smoothing On Sustainability Reporting Disclosure - Dyah Ayu Tri Ratnasari; Zulfikar , Zulfikar (Jurnal Ekonomi, 2024)
Sustainability reporting is a report carried out by the company to meet, fulfill, and fulfill the company's efforts to become a responsible company for all internal and external stakeholders for the company's performance goals towards sustainable development. The purpose of this study was to determine the effect of changes in financial leverage, profitability and revenue smoothing on the disclosure of sustainability reporting. The type of research used in this study is quantitative research by measuring the hypothesis. The population in this study was obtained from data from manufacturing companies that publish financial statements and annual reports on the Indonesia Stock Exchange (IDX) and the company's official website for the period 2020-2022. Sampling method using purposive sampling, and the data used in this study are separate data. The final sample results in this study were 48 companies. The results showed that financial leverage has no effect on the implementation of sustainability reporting, while profitability and income smoothing affect the sustainability reporting disclosure.